Experimental Research on Wind-Induced Flag-Swing Piezoelectric Energy Harvesters. (7th October 2021) - Liu, Jianjun; Chen, Xianghua; Chen, Yujie; Zuo, Hong; Li, Qun
Abstract : Piezoelectric cantilever beams, which have simple structures and excellent mechanical/electrical coupling characteristics, are widely applied in energy harvesting. When the piezoelectric cantilever beam is in a wind field, we should consider not only the influence of the wind field on piezoelectric beam but also the electromechanical coupling effect on it. In this paper, we design and test a wind-induced flag-swing piezoelectric energy harvester (PEH). The piezoelectric cantilever beam may vibrate in the wind field by affixing a flexible ribbon to the free end as the windward structure. To fulfill the goal of producing electricity, the flexible ribbon can swing the piezoelectric cantilever in a wind-induced unstable condition. The experimental findings demonstrate that the flag-swing PEH performs well in energy harvesting when the wind field is excited. When the wind speed is 15 m/s, the peak-to-peak output AC voltage may reach 13.88 V. In addition, the voltage at both ends of the closed-loop circuit's external resistance is examined. The maximum electric power of the PEH may reach 43.4  μ W with an external resistance of 650 kΩ. After passing through the AC-DC conversion circuit, the flag-swing PEH has a steady DC voltage output of 1.67 V. The proposed energy harvester transforms wind energy from a wind farm into electrical energy for supply to low-power electronic devices, allowing for the creation and use of green energy to efficiently address the issue of inadequate energy.